PENGARUH KESELAMATAN KESEHATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DIVISI FITTING PT SURYA TOTO INDONESIA Tbk - Ahmad Mursalin (Al Hasanah Barokah Foundation, 2025)
The purpose of this study was to determine the effect of occupational health safety (K3) and work discipline on employee performance in the fitting division at PT. Surya Toto Tbk, Serpong Tangerang both partially and simultaneously. The method used is a quantitative method. The technique used is nonprobability sampling using a sample of 109 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study are simple linear regression calculations, on occupational health safety (K3) (X1) against performance (Y), then the regression equation Y = 11,530 + 0.732 X1 can be obtained. And work discipline (X2) Against performance (Y) then the regression equation Y = 14,283 + 0.679 X2 can be obtained. Simultaneously occupational health safety (K3) and work discipline affect employee performance with regression calculations obtained the equation Y = 10,409 + 0.249 X1 + 0.512 X2. The correlation coefficient of 0.788 means that the two variables have a strong relationship. The determination coefficient value is 62.2%. Hypothesis testing (t- test) obtained a calculated t value> t table or 96.071> 3.07. Thus, H0 is rejected and H3 is accepted, this indicates that there is an influence of occupational health safety (K3) and work discipline on employee performance in the fitting division PT. Surya Toto Indonesia Tbk. Serpong Tangerang.